Availability Of Human Resources In Halal Certification Testing - R Sabrina (International Journal Reglement & Society (IJRS), 2023)
Based on Indonesian laws and regulations, products that enter, circulate and are traded in Indonesian territory must be halal certified. Thus, product producers including overseas producers are competing to certify their products as halal, considering that Indonesia's huge population with majority Muslim population are a very large market share. Indonesian producers themselves, which are very large in number, must carry out halal certification for their products. Indonesian UKM and IKM products alone easily reach 66 million products. The actor who plays an important role in inspecting and testing product halalness is the halal auditor. The number of halal auditors in Indonesia until 2022 is still very small, namely 965 people, not comparable to the number of products to be certified. So it can be said that there is an imbalance between the number of Indonesian products and available halal auditors.